PENGARUH PENAGIHAN PAJAK DENGAN SURAT TEGURAN DAN SURAT PAKSA TERHADAP KEPATUHAN WAJIB PAJAK DI LINGKUNGAN KANWIL DJP JAWA TENGAH I DAN JAWA TENGAH II - Fahim Rosyidi (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2014)
The purpose of this research is to determine the effect of tax addiction with admission letter and enforcement letter toward tax payer compliance. The method that be used in this research is multiple linier regression which test using SPSS Program In this research, the sample is taken from admission letters and enforcement letter that issued by tax office in the Directorate General of Taxation Central Java I and Central Java II Territory during period 2010 and 2011. The method for choosing the sample is nonprobability, choosing sample based on simplycity Based on the result of the research, shows that the result of hypothesis partially (t-test) get the significancy variable score admission letter and enforcement letter is 0,003 and 0,001 smaller than 0,05. So its proved that admission letter and enforcementletter have significant influence toward tax payer compliance. Determination coefficient shows 0,324 or 32,4% means 32,4% tax payer compliance is influenced by admission letter and enforcement letter.